Strengthening family resilience during accompanied humanitarian assignments - Pepall, Elisa Catherine (Curtin University, 2014)
This qualitative study identifies the dominant challenges faced by accompanying families in the humanitarian INGO sector and proposes recommendations that organisations and families can implement to promote greater family resilience. An under-researched population, the study advocates for greater acknowledgement and supports for expatriate humanitarian families in recognition of the significant impact they have on employee performance, retention, and organisational commitment. A model of factors influencing humanitarian expatriate family adjustment and enhanced resilience is also proposed.